Gender diversity in bank boardrooms and green lending: Evidence from euro area credit register data - Leonardo Gambacorta; Livia Pancotto; Alessio Reghezza; Martina Spaggiari (European Central Bank (ECB), 2022)
Do female directors on banks' boards influence lending decisions toward less polluting firms? By using granular credit register data matched with information on firm-level greenhouse gas (GHG) emission intensities, we isolate credit supply shifts and find that banks with more gender-diverse boards provide less credit to browner companies. This evidence is robust when we differentiate among types of GHG emissions and control for endogeneity concerns. In addition, we also show that female director-specific characteristics matter for lending behavior to polluting firms as better-educated directors grant lower credit volumes to more polluting firms. Finally, we document that the "greening" effect of the female members in banks' boardrooms is stronger in countries with more female climate-oriented politicians.
Keywords: G01; G21; G30; Q50; 330; GHG emissions; Gender; Board diversity; Credit registry; Bank lending